2014
DOI: 10.1186/1471-2334-14-480
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the reproduction number for seasonal, pandemic, and zoonotic influenza: a systematic review of the literature

Abstract: BackgroundThe potential impact of an influenza pandemic can be assessed by calculating a set of transmissibility parameters, the most important being the reproduction number (R), which is defined as the average number of secondary cases generated per typical infectious case.MethodsWe conducted a systematic review to summarize published estimates of R for pandemic or seasonal influenza and for novel influenza viruses (e.g. H5N1). We retained and summarized papers that estimated R for pandemic or seasonal influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
392
3
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(450 citation statements)
references
References 118 publications
45
392
3
10
Order By: Relevance
“…Despite distinct phylogenetic histories, PCV3a and PCV3b exhibited similar Re values of 3.08 (PCV3a, 95% HPD: 0.82–7.96) and 1.82 (PCV3b, 95% HPD: 0.63–4.86) (Figure S2, Supporting Information) based on epidemiological modeling in 2016. This suggests the potential to become endemic in pigs, at least if compared to human influenza viruses 37. Considering the limited number of sequences for 2015 and 2017, the Re value of 2016 was considered valid.…”
Section: Resultsmentioning
confidence: 99%
“…Despite distinct phylogenetic histories, PCV3a and PCV3b exhibited similar Re values of 3.08 (PCV3a, 95% HPD: 0.82–7.96) and 1.82 (PCV3b, 95% HPD: 0.63–4.86) (Figure S2, Supporting Information) based on epidemiological modeling in 2016. This suggests the potential to become endemic in pigs, at least if compared to human influenza viruses 37. Considering the limited number of sequences for 2015 and 2017, the Re value of 2016 was considered valid.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, most influenza studies are based on the 1918 and 2009 pandemics (Biggerstaff et al, 2014), so there is still insufficient information on ILI dynamics. Tamerius et al (2011) have reviewed the effect of seasonality, human immunity and virus survival on the spread of respiratory viruses.…”
Section: Recognised Thatmentioning
confidence: 99%
“…Studies have shown that 5-20% of the US population is infected with influenza every year and that 3000-49000 people die due to diseases associated with influenza every year (8 We determined the prevalence of H3N2 pneumonia as 10.1% in all pneumonia patients treated in our clinic. Apisarnthanarak et al (10) examineda total of 145 cases in the study to compare the risk factors of patients with H3N2 and H5N1 pneumonia and reported that the mean age of the patients with H3N2 pneumonia was 72; the proportion of males was 50%; the proportion of females was 50%; the first distinct symptoms of the majority of the cases (90%) were lung symptoms such as cough, phlegm, and shortness of breath; and the concomitant diseases were lung diseases (50%), diabetes mellitus (30%), cardiovascular diseases (20%), and cerebrovascular diseases (10%), and they also reported a close-ratio (7%) to our study in terms of the incidence of H3N2 pneumonia in their study.…”
Section: Discussionmentioning
confidence: 99%